Efectividad del Programa Educativo "Preveniendo la Diarrea" En El Nivel de Conocimiento de las Madres de Pre-Escolares, 2014 - Amaya Jara, Deysi Aracely (2015)
The present research pre - experimental, was held at the Miramar Sector - Las Palmeras, Province of Pacasmayo, during the months of October to December 2014, in order to determine the effectiveness of the educational program "Preventing Diarrhea" in the level of knowledge of mothers of preschoolers. The sample consisted of 40 mothers selected according to inclusion criteria. The questionnaire "level of knowledge about prevention of acute diarrheal disease" applied before and after the educational program was used for data collection. The data were tabulated and presented in tables. To analyze the statistical test "t student" was used. From the discussion of the results the following conclusions: Before application of the Educational Program 68 percent showed a level of bad knowledge. After application of the Educational Program, 73 percent had a good level of knowledge. The educational program "Preventing diarrhea" was effective to improve the level of knowledge of mothers of preschool significantly Keywords: Educational Program, diarrhea, Knowledge of mothers